2011
DOI: 10.1021/jp203599g
|View full text |Cite
|
Sign up to set email alerts
|

Viability of Clathrate Hydrates as CO2 Capturing Agents: A Theoretical Study

Abstract: Capture and sequestration of green house gas CO(2) is a major challenge for scientists and identifying right materials for this purpose is a task of outstanding importance. Through reliable computational studies, we have demonstrated that the clathrate cages (5(12), 4(3)5(6)6(3), 5(12)6(2), 5(12)6(4), and 5(12)6(8)) have a great potential to store CO(2). All the considered clathrates and their CO(2) inclusion complexes are optimized at B3LYP/6-31G(d) level of theory. The impact of DFT-D, M05-2X, and MP2 functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
62
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(64 citation statements)
references
References 51 publications
2
62
0
Order By: Relevance
“…However, these methods are based on the decomposition of the hydrates by external stimulations, which may lead to geological disasters such as earthquakes and submarine landslides [11][12][13][14]. Alternatively, the CO 2 replacement technique has been widely studied as an economically viable and environmentally friendly production method [15][16][17][18], which also provides a way to store CO 2 for a long term [19,20]. Although the replacement reaction will significantly depend on the experimental conditions [15,21], experimental studies have suggested that at least 60% of CH 4 can be recoverable through the direct injection of CO 2 into CH 4 hydrate layers [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…However, these methods are based on the decomposition of the hydrates by external stimulations, which may lead to geological disasters such as earthquakes and submarine landslides [11][12][13][14]. Alternatively, the CO 2 replacement technique has been widely studied as an economically viable and environmentally friendly production method [15][16][17][18], which also provides a way to store CO 2 for a long term [19,20]. Although the replacement reaction will significantly depend on the experimental conditions [15,21], experimental studies have suggested that at least 60% of CH 4 can be recoverable through the direct injection of CO 2 into CH 4 hydrate layers [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…49 Molecular quantum-chemical computations, where the guest molecules and the cages from the hydrate structures are represented by cluster models, is an efficient way to study host-guest interactions. 30-31, 40-41, 44, 49-52 However, in earlier studies it has been seen that unreasonable deformations of the models of water cavities in some cases occur, 53 and some water cage structures have been optimized with the oxygen atoms fixed. 54 This behavior can be avoided by employing a proper low-energy H-bond network.…”
Section: Introductionmentioning
confidence: 99%
“…Clathrate hydrates have attracted great attention, because they can serve as a possible source of energy [6][7][8] and as a potential medium for gas storage and transportation [9][10][11]. Therefore, an improved understanding of their structural stability is important for many technology applications, e.g., estimating potential effects of hydrates on global climate change [5,12], preventing hydrate blockages in pipelines [13][14], and promoting hydrate formation in gas storage [15][16][17].…”
Section: Introductionmentioning
confidence: 99%